An Unusual Case of Metastatic Tubercular Endophthalmitis - Meenakshi Kabra; Sarita Beri; Rajiv Garg; Pamela d’souza; Rajesh Jain; Anita Nangia; Sanjay Kumar Mishra (Delhi Journal of Ophthalmology)
Tuberculosis is prevalent in developing countries like India, however ocular tuberculosis is a diagnosis of exclusion. This unusual case is of an 18 year old patient of pulmonary Kochs who presented to the out patient department of our hospital with unilateral acute pain in right eye with the marked diminuition of vision of 3 days duration. On Examination his vision in Right eye was PL-negative. This was preceded by gradual painful loss of vision in the right eye for the past two months duration for which he was already taking medication. He was diagnosed as a case of endophthalmitis with secondary glaucoma and ciliary and intercalary staphyloma in R/E. His eye was eviscerated. On the basis of clinical presentation, radiological and histopathological findings diagnosis of Tuberculous endophthalmitis was therefore confirmed.